Pengujian Model “Sliperry Slope” Dalam Kepatuhan Wajib Pajak - Iwan Sidharta (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
The aim of this study was to test the slippery slope model in the taxpayer compliance framework. The method used in this research is quantitative analysis method by doing confirmatory factor analysis testing where the technique used in collecting data is done through questionnaires and sampling technique with nonprobability sampling counted 167 respondents. Based on the results obtained proved that the dimension of trust and dimension of power is the compulsory taxpayer form factor. The trust dimension can explain taxpayer compliance as big as the dimension of the power can explain to the extent that the overall dimension can account for 62,61% of taxpayer compliance.